OBSCN Mutations Associated with Dilated Cardiomyopathy and Haploinsufficiency - Marston,SB; Montgiraud,C; Munster,AB; Copeland,O; Choi,O; dos,Remedios C; Messer,AE; Ehler,E; Knoell,R (PLOS One, 2015)
BackgroundStudies of the functional consequences of DCM-causing mutations have been limited to afew cases where patients with known mutations had heart transplants. To increase the numberof potential tissue samples for direct investigation we performed whole exon sequencingof explanted heart muscle samples from 30 patients that had a diagnosis of familial dilatedcardiomyopathy and screened for potentially disease-causing mutations in 58 HCM orDCM-related genes.ResultsWe identified 5 potentially disease-causing OBSCN mutations in 4 samples; one samplehad two OBSCN mutations and one mutation was judged to be not disease-related. Alsoidentified were 6 truncating mutations in TTN, 3 mutations in MYH7, 2 in DSP and one eachin TNNC1, TNNI3, MYOM1, VCL, GLA, PLB, TCAP, PKP2 and LAMA4. The mean level ofobscurin mRNA was significantly greater and more variable in healthy donor samples thanthe DCM samples but did not correlate with OBSCN mutations. A single obscurin proteinband was observed in human heart myofibrils with apparent mass 960 ± 60 kDa. The threesamples with OBSCN mutations had significantly lower levels of obscurin immunoreactivematerial than DCM samples without OBSCN mutations (45±7, 48±3, and 72±6% of controllevel).Obscurin levels in DCM controls, donor heart and myectomy samples were the same.ConclusionsOBSCN mutations may result in the development of a DCM phenotype via haploinsufficiency.Mutations in the obscurin gene should be considered as a significant causal factorof DCM, alone or in concert with other mutations.